Toll-like receptor signaling in multiple myeloma cells promotes the expression of pro-survival genes B-cell lymphoma 2 and MYC and modulates the expression of B-cell maturation antigen - Tryggestad, Synne Stokke; Roseth, Ingrid Aass; Aass, Kristin Roseth; Ørning, Nadia Elise Helene; Mjelle, Robin; Hella, Hanne; Standal, Therese (Frontiers in Immunology, 2024)
Infections are common in the plasma cell cancer multiple myeloma (MM) due to disease-related immune deficiencies and cancer treatment. Myeloma cells express TLRs, and TLR activation has been shown to induce proliferative and pro-survival signals in the cancer cells. MM is a complex and heterogenous disease, and expression levels of TLRs as well as downstream signaling components are likely to differ between patients. We here show that in a large cohort of patients, TLR1, 4, 6, 9 and 10 are the most highly expressed in primary CD138 + cells. Using a MM cell line expressing TLR4 and TLR9 as a model, we demonstrate that TLR4 and TLR9 activation promoted expression of well-established pro-survival and oncogenes in MM such as MYC, IRF4, NFKB and BCL2. TLR4 and -9 activation inhibited the efficacy of proteasome inhibitors bortezomib and carfilzomib, drugs used in the treatment of MM. Inhibiting the autophagosomelysosome protein degradation pathway by hydroxychloroquine (HCQ) diminished the protective effect of TLR activation on proteasome inhibitor-induced cytotoxicity. We also found that TLR signaling downregulated expression of TNFRSF17, the gene encoding for BCMA. MYC, BCL2 and BCL2L1 were upregulated in about 50% of primary cells, while the response to TLR signaling in terms of TNFRSF17 expression was dichotomous as an equal fraction of patients showed upregulation and downregulation of the gene. While proteasome inhibitors are part of first line MM treatment, several of the new anti-MM immune therapeutic drugs target BCMA. Thus, TLR activation may render MM cells less responsive to commonly used anti-myeloma drugs.